Pengaruh Citra Tubuh terhadap Kompetensi Interpersonal pada Remaja Laki-laki yang Mengikuti Member Gym di Kota Padang - Ghani, Muhammad Farhan; Aulia, Prima (YASIN, 2024)
This research aims to determine the influence of body image on interpersonal competence in young men who attend the gym in Padang City. This research uses quantitative methods with a correlational quantitative design. The data collection technique uses Accidental Sampling. The research sample consisted of 272 respondents. The research instrument uses an interpersonal competence scale which is based on aspects of interpersonal competence according to Buhrmester, et al (1998), as well as a body image scale based on aspects developed by Cash & Pruzinsky (2002). The results of the analysis used simple linear regression analysis and the results showed that body image had a positive and significant effect on interpersonal competence in teenage boys who attended the gym in Padang City.